A pilot study of quantitative capillary refill time to identify high blood lactate levels in critically ill patients. Issue 6 (19th August 2014) - Morimura, Naoto; Takahashi, Kohei; Doi, Tomoki; Ohnuki, Takahiro; Sakamoto, Tetsuya; Uchida, Yasuyuki; Takahashi, Hiroki; Fujita, Takashi; Ikeda, Hiroto
Abstract : Introduction: We developed a new device to quantify capillary refill time (CRT) by applying the pulse oximeter principle, and evaluated the correlation between quantitative CRT (Q-CRT) and hypoperfusion status, as represented by blood lactate levels, in critically ill patients. Methods: A pilot study was undertaken in the intensive care unit (ICU) in a tertiary emergency medical centre. While the pulse oxygen saturation sensor was placed on the finger of the patients, transmitted light intensity (TLI) was measured with a pulse oximeter (OLV-3100; Nihon Kohden, Tokyo, Japan) before and during compression of the finger. Q-CRT was defined as the interval from the release of compression to the time when TLI reached 90% of baseline. Results: Q-CRT was analysed in a total of 57 waveforms among 23 patients and statistically correlated with lactate levels (Spearman's rank correlation coefficient, 0.681; p<0.001). The cut-off value of Q-CRT for predicting a lactate level of ≥2.0 mmol/L was 6.81 s (area under the curve (AUC) (95% CI 1.000 (1.000 to 1.000), p<0.001), and the value for predicting a lactate level of ≥4.0 mmol/L was 7.27 s (AUC=0.989 (95% CI 0.954 to 1.000), p<0.001). Conclusions: Q-CRT correlated with blood lactate levels in this pilot study. The most useful threshold for Q-CRT was ∼6–8 s. Further study is needed to investigate the potential role of this modality as a non-invasive predictor of hypoperfusion in the emergency department, ICU and operating room settings.